Relationships between experiential cultural distance, experiential relationship quality and experiential future intentions: the case of Mainland Chinese tourists. Issue 2 (4th March 2021) - Wu, Hung-Che; Chen, Xiaolian; Cheng, Ching-Chan
ABSTRACT: This paper aims at exploring the structural relationships between the dimensions of experiential cultural distance (experiential individualism/collectivism, experiential uncertainty avoidance, experiential power distance, experiential masculinity/femininity), the dimensions of experiential relationship quality (experiential trust and experiential satisfaction) and future experiential intentions. A convenience sample of 683 Mainland Chinese tourists who had taken an international trip for leisure purposes in the past 12 months in Shanghai Pudong International Airport, Shanghai Hongqiao International Airport, Beijing Capital International Airport, Guangzhou Baiyun International Airport and Shenzhen Bao'an International Airport was surveyed. Results will assist destination management in developing and implementing market-orientated service strategies to decrease perceptions of experiential uncertainty avoidance, experiential power distance and experiential masculinity and increase perceptions of experiential individualism, experiential trust and experiential satisfaction in order to promote future experiential intentions.